Reliability of Gingival Blood Sample to Screen Diabetes in Dental Hospital - Koneru, Suneetha (Int J Prev Med, 2015)
BACKGROUND: Early detection and treatment of diabetes mellitus may reduce the burden of diabetes and its complications. Screening of undiagnosed diabetes with gingival blood sample in patients attending to the dental hospital and to check the reliability with standard method. METHODS: Five hundred and fifty new patients age ranged from 30 to 50 years were randomly selected. Of 550 patients examined, gingival blood samples of 454 patients were collected from bleeding site and analyzed with self-monitoring device. Blood glucose values were recorded. In addition, all the patients were advised for the second visit with overnight fasting for fasting Blood glucose assessment. Among them, 442 patients returned for fasting blood glucose assessment in laboratory with blood glucose analyzer. RESULTS: In the total of 454 patients gingival blood glucose assessment with self-monitoring device, 64 patients showed ≥200 mg/dL, which indicates diabetes, and the other 390 patients showed ≤200 mg/dL, which indicates patients are not diabetic. Whereas, the results of the laboratory blood glucose analysis, 24 (5.43%) patients showed ≥126 mg/dL, 36 (8.14%) patients showed 100–125 mg/dL and the other 382 patients are not diabetic. Comparison of blood glucose measurements by two methods showed sensitivity 96.66% and specificity 99.47%. CONCLUSIONS: The results of the present study showed blood obtained from periodontal pocket probing is a reliable sample to screen diabetes in periodontal disease population. Early diagnosis of diabetes in the dental hospitals can help improve the patient's oral health and overall health status by helping patients avoid or reduce complications from diabetes.